Prosthetically guided mandibular reconstruction using a fibula free flap: three-dimensional Bologna plate, an alternative to the double-barrel technique. Issue 4 (April 2023) - Tarsitano, A.; Ceccariglia, F.; Bevini, M.; Breschi, L.; Felice, P.; Marchetti, C.
Abstract: The fibula free flap represents the gold standard for mandibular reconstruction. However, when harvested as a single barrel, this flap does not allow the native mandibular height to be restored, which is required for implant-supported dental rehabilitation of the patient. The aim of this study was to present a new design for a patient-specific three-dimensionally printed reconstructive plate (3DBO-PSI) that positions the fibula bone at the height of the resected mandibular alveolar bone while restoring the mandibular profile to ensure a correct morphological outcome. Twenty patients were enrolled prospectively between January 2019 and May 2022. All patients underwent a segmental mandibular resection and prosthetically guided reconstruction making use of a fibula free flap supported by the 3DBO-PSI. The mean follow-up period was 20 months. All microvascular and implant-related complications were recorded. Microvascular failure occurred in two patients. No PSI-related complications were recorded during the postoperative follow-up. The proposed reconstructive method was found to be reliable and reproducible. In all treated patients, the bony flap appeared to be adequately positioned to maintain the preoperative intermaxillary relationship, as planned. To date, dental rehabilitation has been completed in seven patients.